The philosophy of the Ukrainian ethnic group’s destruction in the Soviet period - Любов Юрченко; Ірина Старовойтова (Cхід)
The phenomenon of the destruction of the Ukrainian ethnic group during the Soviet times of the first half of the 20th century is analyzed. This phenomenon is represented as a consequence of the brutal violence and aggression of the Soviet authorities towards the Ukrainian ethnic group. In modern conditions, most studies of the violence phenomenon note that in the twentieth century mankind was faced with its unprecedented escalation. World War, Genocide, Holocaust, Terror - all these specific forms of violence have not only touched the Soviet Union but have also become an integral part of its history and culture. Violence has penetrated into all spheres of life and has become a universal means of resolving conflicts. However, the enlargement of violence does not yet determine the specificity of the present.